Preclinical transgenic and patient‐derived xenograft models recapitulate the radiological features of human adamantinomatous craniopharyngioma. (17th May 2017) - Boult, Jessica K. R.; Apps, John R.; Hölsken, Annett; Hutchinson, J. Ciaran; Carreno, Gabriela; Danielson, Laura S.; Smith, Laura M.; Bäuerle, Tobias; Buslei, Rolf; Buchfelder, Michael; Virasami, Alex K.; Koers, Alexander; et al.
Abstract: To assess the clinical relevance of transgenic and patient‐derived xenograft models of adamantinomatous craniopharyngioma (ACP) using serial magnetic resonance imaging (MRI) and high resolution post‐mortem microcomputed tomography (μ‐CT), with correlation with histology and human ACP imaging. The growth patterns and radiological features of tumors arising in Hesx1 Cre/+ ;Ctnnb1 lox(ex3)/+ transgenic mice, and of patient‐derived ACP xenografts implanted in the cerebral cortex, were monitored longitudinally in vivo with anatomical and functional MRI, and by ex vivo μ‐CT at study end. Pathological correlates with hematoxylin and eosin stained sections were investigated. Early enlargement and heterogeneity of Hesx1 Cre/+ ;Ctnnb1 lox(ex3)/+ mouse pituitaries was evident at initial imaging at 8 weeks, which was followed by enlargement of a solid tumor, and development of cysts and hemorrhage. Tumors demonstrated MRI features that recapitulated those of human ACP, specifically, T1 ‐weighted signal enhancement in the solid tumor component following Gd‐DTPA administration, and in some animals, hyperintense cysts on FLAIR and T1 ‐weighted images. Ex vivo μ‐CT correlated with MRI findings and identified smaller cysts, which were confirmed by histology. Characteristic histological features, including wet keratin and calcification, were visible on μ‐CT and verified by histological sections of patient‐derived ACP xenografts. The Hesx1 Cre/+ ;Ctnnb1 lox(ex3)/+ transgenic mouse model and cerebral patient‐derived ACP xenografts recapitulate a number of the key radiological features of the human disease and provide promising foundations for in vivo trials of novel therapeutics for the treatment of these tumors.